Konfirmatori Gabungan Pemasaran Jasa terhadap Animo Beli pada Program Studi Teknologi Pembelajaran - David Kristian Susilo; Nugroho Edie Santoso (IPM2KPE, 2022)
This study aims to determine the combined effect of service marketing on buying interest in the learning technology study program. The data analysis method in this study uses a quantitative investigation using the SEM (Structural Equation Modeling) model, the sample data uses the census method. The use of samples in this study were 492 respondents. The authors of this article processed the data using AMOSE version 16.0 programming. The results showed that the combined variables of service marketing, namely product, price, place, promotion, people, process, and physical evidence had a significant effect on buying interest in the Master of Learning Technology (MTP) Program. In conclusion, if students' views about products, prices, places, promotions, people, processes, and physical evidence are good, it will build students' decisions to continue their education in the Learning Technology Study Program, Universitas PGRI Argopuro Jember and vice versa. Keywords: Confirmatory, Combined, Marketing